2010
DOI: 10.1111/j.1365-2206.2010.00740.x
|View full text |Cite
|
Sign up to set email alerts
|

Young people act as consultants in child-directed research: an action research study in Iceland

Abstract: This paper evaluates an action research study, conducted in Iceland, which involved young service users as consultants to the research. We used participatory group work methods to activate the young people's knowledge and guide social workers in developing their practice. The young people's advice influenced the data generation and analysis, guided the action intervention and contributed to the evaluation. Their emphasis on the quality of relationships and attention to children's concerns was crucial in develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 30 publications
(51 reference statements)
0
12
0
Order By: Relevance
“…It took a participatory approach to involving practitioners who were viewed as active participants drawing upon their substantial experience, insight and skill to produce relevant accounts of their practice in interviews and to develop their practice through change intervention (Fook 2002;Holstein and Gubrium 2004). (For more detail see Kristinsdóttir 2011 andFern 2012a).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It took a participatory approach to involving practitioners who were viewed as active participants drawing upon their substantial experience, insight and skill to produce relevant accounts of their practice in interviews and to develop their practice through change intervention (Fook 2002;Holstein and Gubrium 2004). (For more detail see Kristinsdóttir 2011 andFern 2012a).…”
Section: Methodsmentioning
confidence: 99%
“…The research with this consultancy group was carried out jointly by the British author and an Icelandic researcher based at the University of Iceland (Fern and Kristinsdóttir 2011). These discussions were conducted in a combination of English and Icelandic with interpretation by the Icelandic researcher where necessary.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Holmes et al . , Fern & Kristinsdóttir ); the young people's analysis of their own data and contribution to the writing up process, privileged their perspectives in the final report, as suggested in Lambert et al . (); and we conducted the process on two separate occasions, adding an additional level of rigour and analysis to concept development.…”
Section: Discussionmentioning
confidence: 99%
“…), which concluded that they directly support the translation of knowledge into interventions development, implementation and evaluation; so this approach is essentially practical. Youth participation in research has produced good‐quality, applicable, co‐produced knowledge in diverse contexts, including social work priority clarification in Iceland (Fern & Kristinsdóttir ); human immunodeficiency virus interventions in a Canadian community (Flicker et al . ); African American sexual health education (Guse et al .…”
Section: Introductionmentioning
confidence: 99%